A curse of Beasts and magic - Frost, Jeaniene (Frost, Jeaniene. Beautiful and beastly, 2026)
"Raine Stone is living a nightmare. Ever since she survived the attack that killed her family, she's been hiding a terrible secret--and a Beast inside her. It feeds on violence and chaos, but she restrains its urges by playing vigilante on the city streets. Until one night, Raine uses the Beast's energy to heal an elderly gentleman from a seemingly random attack and discovers a new world of danger-literally. Remington 'Remy' Byrne knows the wall between a realm of deadly mythic creatures and our own world is very fragile. After all, he's the Warden who guards the gateways between them. Raine's Beast contains power that could tip the scales in a sinister plot against Remy's rule-if she allies with him. Will they be friends or foes...or will their dangerous attraction turn into something else? And can our world be saved by their explosive alliance?"--Front jacket flap.